Reversing TGF-β1-induced fibrotic phenotype in human lung fibroblasts using a PROTAC tool derived from an indoline-based HDAC6 inhibitor - Ilaria Cursaro; Valerio Ciccone; Valeria Tudino; Chiara Papulino; Laura Scalvini; Sandra Donnini; Lucia Morbidelli; Luca Bini; Claudia Landi; Chiara Contri; Silvia Pasquini; Fabrizio Vincenzi; et al. (European Journal of Medicinal Chemistry Reports)
Idiopathic pulmonary fibrosis (IPF) is a progressive and debilitating interstitial lung disease characterized by limited therapeutic options, with only two FDA-approved palliative agents currently available. Given its poor prognosis and the high incidence of lung transplantation, there is a pressing need to develop innovative and effective therapeutics. Histone deacetylase 6 (HDAC6) has been identified as a key driver of fibrotic progression in IPF, and selective inhibitors of this isoform were able to revert the fibrotic phenotypes. Proteolysis targeting chimeras (PROTACs) are heterobifunctional molecules that can trigger the degradation of a specific target in cells, including HDAC6 enzyme. Therefore, the application of PROTAC technology may represent a novel therapeutic strategy for IPF. We showcase the design, synthesis, and biological evaluation of a library of first-in-class antifibrotic HDAC6-targeting PROTACs, incorporating our in-house inhibitor 1 as the HDAC6 ligand. Newly developed PROTACs 5a and 5c showed effective degradation of HDAC6 in A549 lung cells and IMR-90 lung fibroblasts. 5a and 5c exhibited significant antifibrotic effects against the TGF-β1 induced fibrotic phenotype on IMR-90 cells, a model that mimics IPF conditions. The generation of putative ternary complexes involving PROTAC molecules, the E3-ligase cereblon (CRBN) and the HDAC6 target protein was supported by molecular modelling techniques, including protein-protein docking and molecular dynamics simulations. Mechanistic investigations, based on pull-down experiments, confirmed that the newly synthetized compounds were able to reduce HDAC6 levels through a proteasome- and CRBN-dependent mechanism as confirmed by experiments with neddylation and proteasome inhibitors. This pioneering exploration of targeted protein degradation in IPF-like conditions provides compelling evidence of its therapeutic promise, paving the way for a broader application of PROTACs in treating rare diseases.